Assessment of agro-ecology, and management practices effect on crop water productivity of major crops at Dapo Watershed, East Wollega Zone, Oromia Regional State - Bane, N. (Ambo University, 2013)
In Ethiopia food production lags behind while population growth increase, poor management of Soil and Water, poor agronomic practices and environmental degradation are wide spread. In the study area, agriculture depends on rain water; however rain water is not evenly distributed spatially and temporally. The general objective of the study is to assess agro-ecology, and crop management practices effect on crop water productivity of major crops. The specific objectives of the study are: - To identify agro-ecologies of the study area according to local classification system, to map land use type of the rainy season, to identify the crop management practices and to evaluate crop water productivity of major crops across agro-ecologies of the study area. The methods used for the study are community based survey after brief visit of five days then questioners were prepared to assess the land use of the district, the common rain water management practices, agronomic practices that the farmers use. Field measurement and statistical methods were used to measure physical and economic crop water productivity; different models like Crop Wat.8 and New loc-clim-1.10 were used to assess the crop water requirement and climate of the area. The result shows that 66% of the watershed is not cultivated while 34% is cultivated. According to local classification system there are three agro ecology zones (Upper zone, Middle Zone and Lower Zone). Middle zone is more productive than lower zone and Upper zone agro ecologies, maize (Zea mays) and teff (Eragrostis teff) are more productive crops while sesame and niger seed are less productive both physically and economically, improved varieties are more productive than local varieties, maximum tillage frequency in the area is four, increase in tillage frequency increased productivity, and precursor crops affect crop water productivity. Physical and economic crop water productivity depends on agro ecology, crop type, crop variety, tillage frequency and precursor crops. So less productive agro ecologies need to be managed properly, maize and tef need to be cultivated to get better economic value, improved crop varieties need to be cultivated to get more physical and economic productivity, to some extent increase in tillage frequency is needed and precursor crops need consideration before planting.